Ascorbate, plant hormones and their interactions during plant responses to biotic stress - Singh Kalpita (PHYSIOLOGIA PLANTARUM, 2024)
Plants can experience a variety of environmental stresses that significantly impact their fitness and survival. Additionally, biotic stress can harm agriculture, leading to reduced crop yields and economic losses worldwide. As a result, plants have developed defense strategies to combat potential invaders. These strategies involve regulating redox homeostasis. Several studies have documented the positive role of plant antioxidants, including Ascorbate (Asc), under biotic stress conditions. Asc is a multifaceted antioxidant that scavenges ROS, acts as a co‐factor for different enzymes, regulates gene expression, and facilitates iron transport. However, little attention has been given to Asc and its transport, regulatory effects, interplay with phytohormones, and involvement in defense processes under biotic stress. Asc interacts with other components of the redox system and phytohormones to activate various defense responses that reduce the growth of plant pathogens and promote plant growth and development under biotic stress conditions. Scientific reports indicate that Asc can significantly contribute to plant resistance against biotic stress through mutual interactions with components of the redox and hormonal systems. This review focuses on the role of Asc in enhancing plant resistance against pathogens. Further research is necessary to gain a more comprehensive understanding of the molecular and cellular regulatory processes involved.